The Efficiency of Melanoidin Based-Waste Degradation with Different Biological Methods - Hafizh Zahra; Ilham Kurniawan; Abdurrahman Hakim (Current Biochemistry, 2020)
Each processing palm fresh fruit bunches (FFB) into Crude Palm Oil (CPO) will produce solid and liquid waste. One of the forms of liquid waste produced is Palm Oil Mill Effluent (POME). POME waste can cause problems for the environment because it has physical characteristics of dark brown color, high density, rich in organic matter, and bad smell. The POME waste color is thought to come from melanoidin, a biopolymer pigment produced by the Maillard reaction of coconut processing. Apart from melanoidin, phenolic components are detected in POME waste, where this group of compounds is toxic. Several studies have shown that Lactobacillus plantarum can reduce the color of POME by 75%. The decolorization process is thought to involve an enzyme as a waste color-changing agent. However, the efficiency associated with these events has not been further investigated. There are three main methods of melanoidin degradation, such as biological, physicochemical, and enzymatic. This study uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) approach in creating a short, concise, and clear summary through various references.